Inhibitory mechanism of fly ash on alkali-silica reactivity of siliceous rock fine aggregate: A case study of Yangxi concrete dam - Jianguo Chen; ZhuoJie Huang; Weilian Du; Yuling Zhu; Mingsheng Shi; Binghan Xue (Case Studies in Construction Materials, 2023)
The fine aggregate of siliceous rock has the advantages of high production efficiency, stable yield and low construction and transportation cost. The Yangxi concrete dam was firstly apply siliceous rock as fine aggregate to a large concrete project of three million m3. However, siliceous rock aggregate has high SiO2 content, which is easy to trigger alkali-silicate reactivity. To investigate the alkali-silica reactivity characteristics of siliceous rock fine aggregate and its inhibitory measures, in this work, we used fly ash, ordinary silicate cement, and siliceous rock fine aggregate to prepare cement mortar. The effects of fly ash admixture on the expansion rate, as well as the flexural and compressive strength of the mortar were investigated by the mortar rod rapid method and mechanical tests. The inhibition mechanism of fly ash on the siliceous rock fine aggregate was analyzed by scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) techniques. The results showed that the addition of 30 % fly ash to the siliceous rock mortar could effectively limit the mortar expansion and its late strength growth was the most rapid. Compared to siliceous rock mortar without fly ash, the FA30 specimen mixed with 30 % fly ash had a denser structure, the hydration products at the ITZ were more closely arranged, and the C-A-S-H gel with a low calcium-silica ratio was generated internally, which could effectively inhibit the ASR of the siliceous rock fine aggregate.